Enhancing the ecological services of agricultural areas for flood mitigation through ecosystem valuation a case study in Brgy. Sta. Ana, Taytay, Rizal - Dayag, John Emmanuel A. (College of Architecture, University of the Philippines Diliman, 2019)
Over the past years, the number of reported flood events has increased significantly which means that the number of people affected by floods and financial, economic, and insured damages have all increased too. Implementation of flood risk management has helped address the devastating impacts of flooding. While this is encouraging, fatalities still remain high where flood events happen, particularly in agricultural areas. In addressing inundation on these areas, a landscape design can be a solution through enhancing the capacities of the site in runoff retention as well as enhance its materials output production. A landscape that uses systems that are made up enhanced ecosystems is designed to alleviate flood hazards through absorption of excess water and increase in agricultural output. Valuation of the regulating services, particularly water retention capacity and provisioning services, particularly crop production between the environmental baseline and the proposed design intervention are quantified through ecosystem valuation methods. The thesis concludes that the landscape design interventions can alleviate the impacts of flooding through increasing the ecosystem services of the site. The proposed design has increased its water retention capacity up to 30 percent, thus, decreasing the hazards of flooding to the farming community located in the site. Furthermore, the agricultural output of the site is enhanced through incorporation of crop production strategies, resulting to an estimated 90 percent increase in crop production.